LuMPIS - A modified luminescence-based mammalian interactome mapping pull-down assay for the investigation of protein-protein interactions encoded by GC-low ORFs - Vizoso Pinto, María Guadalupe (2009)
The GC content is highly variable among the genomes of different organisms. It has been shown that recombinant gene expression in mammalian cells is much more efficient when GC-rich coding sequences of a certain protein are used. In order to study protein-protein interactions in Varicella zoster virus, a GC-low herpesvirus, we have developed a novel luminescence-based maltose-binding protein pull-down interaction screening system (LuMPIS) that is able to overcome the impaired protein expression levels of GC-low ORFs in mammalian expression systems. © 2009 Wiley-VCH Verlag GmbH & Co. KGaA.